Predictors Of Medication Adherence Among Older Adults With Uncontrolled Hypertension - XIANG, XIAOPING; Hengudomsub, Pornpat; Ponpinij, Panicha (วารสารคณะพยาบาลศาสตร์ มหาวิทยาลัยบูรพา, 2025)
This predictive correlational study aimed to examine medication adherence and its influencing factors among Chinese older adults with uncontrolled hypertension. Using simple random sampling, 137 patients aged 60 years and above were recruited from the Department of Cardiology at the Second Affiliated Hospital of Wenzhou Medical University. Data were collected through validated instruments, including the Morisky Medication Adherence Scale (MMAS-8), the Chinese Medication Literacy Scale (C-MLSHP), the Medication Self-Efficacy Scale (MASES-R), and the Multidimensional Social Support Scale (MSPSS). Descriptive statistics and multiple linear regression analyses were conducted. The results indicated a low mean medication adherence score (M = 5.59, SD = 0.98). Medication self-efficacy, medication literacy, and social support combinedly explained 30.8% of the variance in medication adherence (Adjusted R² = 0.308, F(3,133) = 21.185, p < .001). Medication self-efficacy emerged as the strongest predictor (β = 0.431, p < .001), followed by medication literacy (β = 0.240, p < .05). However, social support did not has a significant effect on medication adherence (β = 0.015, p > 0.05). These findings underscore the critical role of medication self-efficacy and literacy in promoting medication adherence among older adults with uncontrolled hypertension and highlight the need for targeted nursing interventions aimed at enhancing these factors to improve health outcomes.